Does stakeholder pressure influence firms environmental, social and governance (ESG) disclosure? Evidence from Ghana - Noha Alessa; John Yaw Akparep; Inusah Sulemana; Andrew Osei Agyemang (Cogent Business & Management, 2024)
In the era of climate change, stakeholders are becoming more concerned about the sustainability disclosure of businesses. However, for developing economies like Ghana, studies on stakeholders' pressure and sustainable development has not received much attention. Hence, this study examines the influence of stakeholders' pressure on sustainability disclosure and employed green technological innovation (GTI) as a mediating factor. The study focused on mining and manufacturing firms because their processes are known to release carbon dioxide, create waste. The data utilize in this study was collected from 383 respondents in Ghana via online questionnaires. PLS-SEM was used to analyze the data and tested the hypothesis for the study using SMART-PLS 4. The results demonstrated that stakeholder pressure substantially improves sustainability disclosure performance. Also, the results revealed that a firm's GTI mediates the connection between stakeholder pressure in terms of shareholder and consumer pressures. However, government pressure and sustainability disclosure were found to be insignificant. The study recommends that managers should incorporate GTI into the product design and manufacturing process since it enables firms not only fulfill their client's needs but also reduce their environmental impacts, like the production of carbon dioxide and solid debris.
Keywords: 650; Developing economy; green technological innovation; stakeholders pressure sustainability disclosure